The intercultural dimension in the adoptive family: educational processes and practices in the formation of multiple belonging - Loredana Paradiso (University of Bologna, 2024)
The adoptive family is a privileged pedagogical observatory of intercultural phenomena in the delicate process of self-recognition as parents and children and the formation of family belonging. A field that questions pedagogy on the intercultural perspective of making a family in order to analyse the role of diversity, of welcoming the Other in the child's identity process co-construction paths. In this paper, attention is focused on parenting skills and on good educational and socio-cultural practices to support family cultural integration processes and of the formation of the child's dual cultural belonging.